Divergent synthetic nucleotide motif recognition pattern: design and development of potent immunomodulatory oligodeoxyribonucleotide agents with distinct cytokine induction profiles - Kandimalla, Ekambar R. (Oxford University Press, 2003)
Unmethylated CpG dinucleotides present within certain specific sequence contexts in bacterial and synthetic DNA stimulate innate immune responses and induce cytokine secretion. Recently, we showed that CpG DNAs containing two 5′-ends, immunomers, are more potent in both regards. In this study, we show that an immunomer containing a synthetic CpR motif (R = 2′-deoxy-7-deazaguanosine) is a potent immunostimulatory agent. However, the profile of cytokine induction is different from that with immunomers containing a natural CpG motif. In general, a CpR immunomer induced higher interleukin (IL)-12 and lower IL-6 secretion. Compared with conventional CpG DNAs, both types of immunomers showed a rapid and enhanced activation of the transcription factor NF-κB in J774 cells. NF-κB activation by CpG DNA corresponded to degradation of IκBα in J774 cells. All three immunostimulatory oligonucleotides activated the p38 mitogen-activated protein kinase pathway as expected. Immunomers containing CpG and CpR motifs showed potent reversal of the antigen-induced Th2 immune response towards a Th1 type in antigen-sensitized mouse spleen cell cultures. Immunomers containing a CpR motif showed significant antitumor activity in nude mice bearing MCF-7 human breast cancer and U87MG glioblastoma xenografts. These studies suggest the ability for a divergent synthetic nucleotide motif recognition pattern of the receptor involved in the immunostimulatory pathway and the possibility of using synthetic nucleotides to elicit different cytokine response patterns.